SOLVATION PROPERTY EFFECT ON CRYS TALLIZATION THROUGH COOLING: Short Communication (Biological Sciences - PJSIR, 2002)
The earlier work (Nayeemuddin et al 2000 a), concerning deri vation of formulae for determination of various parameters such as heat of crystallization , heat transfer/utilization co efficients, in case of crystallization of magnesium sulphate during cooling of sea bittern, was based on linearity of batch/ unsteady state operation.